Growth inhibitory properties of Backhousia myrtifolia Hook. & Harv. and Syzygium anisatum (Vickery) Craven & Biffen extracts against a panel of pathogenic bacteria - Bryant, Krystal; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: B. myrtifolia and S. anisatum are native Australian trees with uses as traditional medicines and bushfoods. Essential oils produced from leaves of these species have reputed antiseptic properties. Despite this, B. myrtifolia and S. anisatum leaf solvent extractions have not been rigorously examined for antibacterial properties against many pathogens. Methods: The antimicrobial activity of aqueous and methanolic leaf extracts of B. myrtifolia and S. anisatum was investigated by disc diffusion and growth time course assays against a panel of pathogenic bacteria. The growth inhibitory activity was quantified by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous B. myrtifolia and S. anisatum leaf extracts inhibited the growth of a wide range of bacterial species. Growth of both gram positive and gram negative bacteria was inhibited the B. myrtifolia and S. anisatum extracts to approximately the same extent. In general, S. anisatum extracts were more potent inhibitors of bacterial growth than were the B. myrtifolia extracts, and (with some noteable exceptions) the methanolic extracts were generally more potent than the aqueous extracts. The B. myrtifolia and S. anisatum extracts were particularly potent inhibitors of P. mirabilis growth, with MIC values as low as 105 µg/mL (aqueous S. anisatum extract). The antibacterial activity of the methanolic B. myrtifolia and S. anisatum extracts were further investigated by growth time course assays which showed significant growth inhibition in cultures of E. coli, K. pneumpniae and P. mirabilis within 1 h of exposure. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indi- cating their safety for internal use as well as for topical uses. Conclusions: The lack of toxicity of the B. myrtifolia and S. anisatum extracts and their growth inhibitory bioactivity against a panel of pathogenic bacteria partially validate Australian Aboriginal usage of these species as antiseptic agent and indicate their potential in the development of antiseptic agents.
Keywords: Backhousia myrtifolia; Syzygium anisatum; Cinnamon myrtle; Anise myrtle; Australian plants; Antibacterial activity; Medicinal plants.